ANALISIS TEGANGAN LANGKAH DAN TEGANGAN SENTUH SERTA PERENCANAAN SISTEM PEMBUMIAN PADA PEMBANGUNAN SUBSTATION VVIP DI BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI BALI - Mirah Mahadewi, Kadek; Janardana, I Gusti Ngurah; Arta Wijaya, I Wayan (Jurnal SPEKTRUM, 2019)
I Gusti Ngurah Rai International Airport Bali previously had a Substation (SS) D which serves the electrical system for the operation of modified Sewage Treatment Plant, however that substation currently under development with the construction of SS VVIP which serves the electrical system for the operation of VVIP buildings and Sewage Treatment Plant. To maintain the security of equipment and humans around the SS VVIP building a good grounding system is needed with a grounding resistance value of <1 Ohm. Because the land at Ngurah Rai Airport is sandy land, the suitable grounding systems are Pelat, Mesh, Grid-Rod groundinh systems [1]. To get an R value <1 Ohm, an analysis of each grounding system is needed, namely Pelat, Mesh, Grid-Rod. The results of the analysis showed that the safest system was the Grid-Rod grounding system with a grounding resistance value of 0.3718 Ohm, a touch voltage value of 223.51 Volt, a step voltage value of 1188.69 Volt and a planning cost of Rp7,712,500. Based on the construction planning data of the SS VVIP Ngurah Rai Airport, the grounding system used is the same as the result of the analysis of the Grid - Rod grounding system.